Polyhexanide as a new antiseptic composition for a dentist - Z. S. Khabadze; D. S. Nazarova; A. A. Kulikova; Yu. A. Generalova; E. S. Shilyaeva; A. P. Kotelnikova (Эндодонтия Today)
Aim. To assess systematically the available scientific evidence about clinical response of using polyhexanide as an antiseptic agent in medicine and dentistry. The properties of polyhexanide – excellent antimicrobial activity, chemical stability and low toxicity – have been studied.